Analisa Pengaruh Foreign Direct Investment terhadap Nilai Tambah Industri Pengolahan di Indonesia - Azwin Alfarizsy, Ahmad; Ekananda, Mahyus (Program Studi Manajemen FEBM UMRAH, 2024)
This study aims to measure the effect of Foreign Direct Investment to value-added of manufacturing industry in Indonesia. This study uses data from 24 manufacturing sub-sectors according to the Indonesian Standard Industrial Classification. The data used in this study are: FDI and PMDN realization data (sourced from BKPM); data of value added, labor, fixed capital, production input costs and labor expenditures (sourced from Central Bureau of Statistic). The estimation method used is Feasible Generalized Least Square with Fixed Effect, with a period of years from 2009 to 2019. The results of this study indicate that FDI and several related variables have a significant positive effect on the value added of the manufacturing industry in Indonesia.